Understanding the impact process of vaccine adoption for COVID-19 - Wenlong Zhu; Hao Zou; Ying Song; Lili Ren; Yingjie Xu (Taylor & Francis Group, 2022)
Vaccination for the novel coronavirus disease 2019 (COVID-19) provides an effective approach for the general improvement of social safety and individual health. To date, few studies have analyzed the adoption of COVID-19 vaccines from an entire impact process perspective. Using the health belief model (HBM) and the valence theory, this research evaluates the impact process of vaccine adoption for COVID-19. The respondents in this study were individuals who have been vaccinated in China. The effective sample included 595 individuals. Four valuable and novel findings are identified through this research. First, neither perceived susceptibility nor perceived severity has a statistically significant impact on the benefits from vaccination, threats from vaccination and self-efficacy. Second, benefits from vaccination produce a significant positive effect on self-efficacy and vaccine adoption. Third, threats from vaccination produce a significant negative effect on self-efficacy and vaccine adoption. Fourth, both self-efficacy and cues to adoption produce a significantly positive impact on vaccine adoption. Our theoretical model, which is the main contribution of this research, indicates that individual vaccine adoption is simply a process that leads from behavioral cognition to behavioral intention, rather than from psychological perception to behavioral cognition and then from behavioral cognition to behavioral intention.